(untitled) (Perner’s Contacts, 2018)
Intelligent transport systems, used for tracking of goods, open up new opportunities to achieve sustainable mobility and create the conditions for a high-quality communication and information society. The paper informs about the tracking systems used in each transport department of Slovakia.